2022
DOI: 10.1136/bcr-2022-250342
|View full text |Cite
|
Sign up to set email alerts
|

Male infant with Noonan syndrome withRAF-1gene mutation who survived hypertrophic cardiomyopathy-induced fatal heart failure and uncontrollable arrhythmias

Abstract: Noonan syndrome (NS) is a congenital disease with characteristic facial features as well as heart disease, short stature and thoracic abnormalities. More than eighty per cent of patients with NS show several cardiac disorders including pulmonary valvular stenosis, hypertrophic cardiomyopathy (HCM) and/or atrial septal defects. HCM is a serious cardiac comorbidity in patients with NS, especially in those who are diagnosed within 6 months of age with congestive heart failure. Arrhythmia with or without HCM in NS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…Studies have suggested that males with NS may be more likely to have more severe cardiac manifestations, including a higher incidence of hypertrophic cardiomyopathy and aortic valve stenosis, compared to females with NS (3,35,65). Similarly, few studies indicated that males had a higher incidence of pathogenic variants in the RAF1 gene, a less common genetic mutation associated with NS (66)(67)(68)(69). However, other studies suggested no significant sex differences in the prevalence or severity of cardiac abnormalities in NS patients (16,70).…”
Section: Sex Dimorphism In Rasopathy-induced Cardiomyopathy In Ns And...mentioning
confidence: 99%
“…Studies have suggested that males with NS may be more likely to have more severe cardiac manifestations, including a higher incidence of hypertrophic cardiomyopathy and aortic valve stenosis, compared to females with NS (3,35,65). Similarly, few studies indicated that males had a higher incidence of pathogenic variants in the RAF1 gene, a less common genetic mutation associated with NS (66)(67)(68)(69). However, other studies suggested no significant sex differences in the prevalence or severity of cardiac abnormalities in NS patients (16,70).…”
Section: Sex Dimorphism In Rasopathy-induced Cardiomyopathy In Ns And...mentioning
confidence: 99%